Vascular characteristics in young women—Effect of extensive endurance training or a sedentary lifestyle. (19th February 2018) - Bjarnegård, N.; Länne, T.; Cinthio, M.; Ekstrand, J.; Hedman, K.; Nylander, E.; Henriksson, J.
Abstract: Aim: To explore whether high‐level endurance training in early age has an influence on the arterial wall properties in young women. Methods: Forty‐seven athletes (ATH) and 52 controls (CTR), all 17‐25 years of age, were further divided into runners (RUN), whole‐body endurance athletes (WBA), sedentary controls (SC) and normally active controls (AC). Two‐dimensional ultrasound scanning of the carotid arteries was conducted to determine local common carotid artery (CCA) geometry and wall distensibility. Pulse waves were recorded with a tonometer to determine regional pulse wave velocity (PWV) and pulse pressure waveform. Results: Carotid‐radial PWV was lower in WBA than in RUN ( P < .05), indicating higher arterial distensibility along the arm. Mean arterial pressure was lower in ATH than in CTR and in RUN than in WBA ( P < .05). Synthesized aortic augmentation index (AI@75) was lower among ATH than among CTR (−12.8 ± 1.6 vs −2.6 ± 1.2%, P < .001) and in WBA than in RUN (−16.4 ± 2.5 vs −10.7 ± 2.0%, P < .05), suggesting a diminished return of reflection waves to the aorta during systole. Carotid‐femoral PWV and intima‐media thickness (IMT), lumen diameter and radial distensibility of the CCA were similar in ATH and CTR. Conclusion: Elastic artery distensibility and carotid artery IMT are not different in young women with extensive endurance training over several years and in those with sedentary lifestyle. On the other hand, our data suggest that long‐term endurance training is associated with potentially favourable peripheral artery adaptation, especially in sports where upper body work is added. This adaptation, if persisting later in life, could contribute to lower cardiovascular risk.